Risk and Preserve Life: Human Rights, Armed Sociopolitical Conflict and Social Work in Colombia - Castaño-Orozco, Cristian Sebastian; Patiño-Martínez, Ricardo (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This article seeks to create an overview of the movement for the defense of Human Rights in Colombia, in relation to the development of a counterinsurgency strategy as an opportunity for the professional exercise of Social Work position. We examine a series of possibilities of actions within the training and professional performance of a social worker to contribute to the construction of peace and social justice in Colombia.